Serine protease P-IIc is responsible for the digestion of yolk proteins at the late stage of silkworm embryogenesis. (July 2016) - Wang, Dandan; Zhang, Yan; Dong, Zhaoming; Guo, Pengchao; Ma, Sanyuan; Guo, Kaiyu; Xia, Qingyou; Zhao, Ping
Abstract: In silkworms, yolk proteins comprise vitellin, egg-specific protein and 30K proteins, which are sequentially degraded by endogenous proteases strictly regulated during embryogenesis. Although the process has been extensively investigated, there is still a gap in the knowledge about the degradation of silkworm yolk proteins on the last two days of embryonic development. In the present study, we isolated and purified a gut serine protease P-IIc, which demonstrated optimal activity at 25 °C and pH 11. Semi-quantitative RT-PCR combined with western blotting showed that P-IIc was actively expressed and significantly accumulated in the gut on the last two days of embryogenesis. When natural yolk proteins were incubated with P-IIc in vitro, vitellin and ESP were selectively degraded. P-IIc also demonstrated activity towards 30K proteins as evidenced by rapid and complete digestion of BmLP1 and partial digestion of BmLP2 and BmLP3. Furthermore, RNAi knockdown of P-IIc in silkworm embryos significantly reduced the degradation rate of residual yolk proteins on embryonic day 10. Taken together, our results indicate that P-IIc represents an embryonic gut protease with a relatively broad substrate specificity, which plays an important role in the degradation of yolk proteins at the late stage of silkworm embryogenesis. Graphical abstract: Highlights: Protease P-IIc was purified from the larval gut by gel filtration chromatography. Protease P-IIc was highly expressed on the last day of the embryo and newly hatched larvae. Protease P-IIc could degrade 30K protein BmLP1 and Vtn fragments on the last day of embryogenesis. Downregulation of protease P-IIc affected the utilization of BmLP1 on the last day of embryogenesis.